BINARISM IN THE SYSTEM OF CHARACTERS OF THE LATGALIAN ZOOMORPHIC ANECDOTES - Belasova, Inga (Via Latgalica, 2010)
Character profile and the system of images as a whole demonstrates the binary structure based on the mythological tradition. Double character of the nature motif pervades the folklore tradition, which is the most demonstratively revealed by the twin motif, where two brothers at the same time are both opposites and complement each other. The paper has applied the structural semiotic method, using opinions of the Russian philologist and culture historian Eliza Meletinskii (Елеазар Мелетинский) on the connection of binary oppositions with the mythological metaphorism and pairs of binary opposition. Purpose – to describe the binarism as an underlying principle for revealing the genre specifics of the Latgalian zoomorphic anecdote at the level of images.Struggle of opposites has a special sense in mythological consciousness. Diversity of social roles in a real life can create one character, as well as features that functions as a contrast, by becoming embodied in evil or consistently positive characters, within an anecdote can impersonate a whole ambivalent image. The mythical twin rivalry theme is very topical in the folklore tradition, since existence of pair of twins depicts a situation when two beings create one spiritual body, but at the same time the mysterious twin pair exists in separate contradictory categories.In the context of binary opposition, personal identity problem of the hero of zoomorphic anecdotes does not stem from the world outlook, philosophy or culture, but everyday life, it is a practical problem, so to speak, choice of everyday role, place and behavior. A combination of the cliché features in a particular character serves as one of the stereotype-forming directions. Characters of the Latgalian zoomorphic anecdotes have no clearly defined understanding of their place in society, because they represent stereotypical roles of the modern world. Characters’ inherent ability to change their traditional, ideological and functional load, as justified by the progressive principle of mediation, is considered to be one of the most important features in Latgalian anecdotes about animals.Specific research reflects also the fact that tricksterism in Latgalian zoomorphic anecdotes is a universal component of typical characters. Orientation of a trickster towards opposites and the destruction of the opposition reflects ambivalence of characters and describes them as promulgators of revolutionary ideas. Significantly enough, the particularity of a trickster can be depicted in two ways – explicitly: the character displayed in the text, and implicitly: the anecdote teller and the listener, who immanently identifies themselves with the character. This can be explained by hidden or open desire inherent in the tellers of anecdotes and the recipients to express the desires existing in subconsciousness.Upon inquiry into the impact of trickster on the characters and its place in the system of images as a whole, binary structure based on a mythological tradition is unfold, where features of the mythical twin pair in characters of the Latgalian anecdotes is depicting their controversial nature. This has to do with the personal identity problem of images, which has to be searched for in choice of familiar role and behavior. Each situation played in anecdotes compactly illustrates the collision of opinions, notions or values, providing for the winner and loser positions, contributing to a possible change in the conventional concepts. In Latgalian anecdotes about animals, the place of a character in the system of images is often based on a binary opposition relationship the strongest – the weakest, where the physically strongest image of the anecdote do not always owns the anecdote teller’s – the listener's sympathy.Binary oppositions in Latgalian zoomorphic anecdotes have peculiar specifics, which is due to the fact that mainly animal characters are active in the zoomorphic anecdotes. Consequently, the binary oppositions in anecdotes about animals are of more archaic and expanded nature, which is accompanied by greater generalization and certain mythological deeper layer as in other genres of anecdotes.